RIRS AND MINI-PCNL IN MANAGEMENT OF KIDNEY STONE: A COMPARATIVE STUDY - AKHTAR, M; KHAN, MU; USMAN, HM; RAZA, QH; ASLAM, N; ULLAH, MS (Biological and Clinical Sciences Research Journal, 2022)
To compare results of retrograde intrarenal surgery and minimally invasive percutaneous nephrolithotomy in older patients, a retrospective study was conducted at the Department of Nephrology & Urology of MMDC&Ibn-e-Sina Hospital Multan from January 2021 to January 2022. The study included 135 patients, 65 underwent M-PCNL while 70 underwent RIRS. Gender, age, BMI, ASA scores, stone location and size, ESWL history, SFR and relevant parameters were recorded. Characteristics like gender, age, BMI, stone size and location, HU and ESWL history did not vary significantly in both group (p>0.05). Mean ASA scores and the data of ASA I and ASA II in both groups was also similar (p>0.05). Postoperative Clavien complications, operation time and postoperative transfusion rate in both groups did not vary significantly (p>0.05). M-PCNL patients had greater post operative SFR values (p<0.05). Retrograde intrarenal surgery and minimally invasive percutaneous nephrolithotomy arerecommended methodsin treatment of kidney stones.